Repair cell first, then regenerate the tissues and organs - Fu, Xiao-Bing (Mil Med Res, 2021)
Wound healing, tissue repair and regenerative medicine are in great demand, and great achievements in these fields have been made. The traditional strategy of tissue repair and regeneration has focused on the level of tissues and organs directly; however, the basic process of repair at the cell level is often neglected. Because the cell is the basic unit of organism structure and function; cell damage is caused first by ischemia or ischemia-reperfusion after severe trauma and injury. Then, damage to tissues and organs occurs with massive cell damage, apoptosis and even cell death. Thus, how to achieve the aim of perfect repair and regeneration? The basic process of tissue or organ repair and regeneration should involve repair of cells first, then tissues and organs. In this manuscript, it is my consideration about how to repair the cell first, then regenerate the tissues and organs.